2011
DOI: 10.1523/jneurosci.0285-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Sensory and Associative Microcircuitry in Primary Olfactory Cortex

Abstract: The three-layered primary olfactory (piriform) cortex is the largest component of the olfactory cortex. Sensory and intracortical inputs converge on principal cells in the anterior piriform cortex (aPC). We characterize organization principles of the sensory and intracortical microcircuitry of layer II and III principal cells in acute slices of rat aPC using laser-scanning photostimulation and fast two-photon population Ca 2ϩ imaging. Layer II and III principal cells are set up on a superficial-to-deep vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 46 publications
3
51
1
Order By: Relevance
“…Excitatory neurons in layer 2 can be subdivided in semilunar (upper layer 2) and superficial pyramidal neurons (lower layer 2), whereas those in layer 3 comprise a few deep pyramidal cells and scattered multipolar spiny glutamatergic neurons (Haberly 1983;Suzuki and Bekkers 2006;Bekkers and Suzuki 2013). Although they are embedded in the same basic connectivity scheme, semilunar and superficial pyramidal cells receive different ratios of afferent to associational inputs and may therefore belong to distinct functional sub-circuits (Suzuki and Bekkers 2011; but see Poo and Isaacson 2011), consistent with morphological differences between their dendritic trees and their laminar position (Wiegand et al 2011). Although data on subpopulations of principal cells in DCx are few, analysis of Golgi-stained material also revealed different morphological classes of spiny neurons at different laminar and sublaminar positions in reptilian cortex (Ulinski 1977;Desan 1984) PCx and DCx pyramidal neurons are also similar with respect to their dendritic electrophysiological properties, suggesting comparable integrative properties at the subcellular level (Larkum et al 2008;Bathellier et al 2009).…”
Section: Vertical Connectivitymentioning
confidence: 74%
“…Excitatory neurons in layer 2 can be subdivided in semilunar (upper layer 2) and superficial pyramidal neurons (lower layer 2), whereas those in layer 3 comprise a few deep pyramidal cells and scattered multipolar spiny glutamatergic neurons (Haberly 1983;Suzuki and Bekkers 2006;Bekkers and Suzuki 2013). Although they are embedded in the same basic connectivity scheme, semilunar and superficial pyramidal cells receive different ratios of afferent to associational inputs and may therefore belong to distinct functional sub-circuits (Suzuki and Bekkers 2011; but see Poo and Isaacson 2011), consistent with morphological differences between their dendritic trees and their laminar position (Wiegand et al 2011). Although data on subpopulations of principal cells in DCx are few, analysis of Golgi-stained material also revealed different morphological classes of spiny neurons at different laminar and sublaminar positions in reptilian cortex (Ulinski 1977;Desan 1984) PCx and DCx pyramidal neurons are also similar with respect to their dendritic electrophysiological properties, suggesting comparable integrative properties at the subcellular level (Larkum et al 2008;Bathellier et al 2009).…”
Section: Vertical Connectivitymentioning
confidence: 74%
“…As noted earlier, SL cells are most likely the first neurons in the feedback inhibitory circuit because they receive the strongest LOT input (Suzuki and Bekkers, 2011;Wiegand et al, 2011). Additional evidence comes from measurements of firing latency.…”
Section: Synaptic and Firing Latencies Confirm The Involvement Of Fasmentioning
confidence: 89%
“…We have recently shown that SL cells receive the strongest aff input from the LOT (Suzuki and Bekkers, 2011; see also Wiegand et al, 2011); hence, it is likely that SL cells drive IN2 to generate feedback inhibition (Fig. 1 A).…”
Section: Stimulus-response Plots Implicate Fastspiking Cells In Feedbmentioning
confidence: 90%
See 1 more Smart Citation
“…In the APC, principal excitatory neuron classes differ in laminar location and in the proportion of afferent vs. intracortical excitatory input received (34)(35)(36)(37). Within L2, semilunar cells (SLCs) receive predominantly afferent excitation, whereas superficial pyramidal cells (sPCs) receive weaker afferent and stronger intracortical excitatory drive.…”
mentioning
confidence: 99%